Female Physicians And Professional Careers - Tafo, Ghislaine Neuilly Ngniee; Diarra, Yaye; Traoré, Seydou Tidiane (Advances in Social Sciences Research Journal, 2023)
Since Peseshet, the first known female physician in the world, the number of female physicians has not stopped growing. In USA, they represent 36,3% of practicing physicians, while in Mali, they represent only 16%. Unfortunately, female physicians are still under-represented in the highest positions of the medical hierarchy. It is often found that family responsibilities, can have an impact on their careers. Our objective was to determine the conditions of practice of women physicians as well as their perception on the evolution of their career. To achieve this goal, we conducted a prospective, cross-sectional study on a sample of 123 Malian women physicians obtained by a survey form. We were able to observe that only 34.18% of female physicians were specialists, only 14% of teaching and research positions are held by women, and this percentage decreases as one moves up the ranks. The majority 97.6% have professional ambitions. 12.2% do not feel encouraged to do so, mainly by their families. 78.9% are not satisfied with their working conditions and almost half, 45.5%, have felt discriminated against in favor of their male colleagues. 25.2% have already been harassed morally/physically, mainly (67.7%) by their male colleague. The difficulties are such that 26.5% are considering changing their professional path. The results show that although the number of women doctors is increasing over time, they still have various difficulties in reaching the top of the hierarchy, although they overwhelmingly express the desire for professional progression.